Efektif Pengetahuan dan Sikap Masyarakat Dalam Upaya Pencegahan Tuberkulosis: Effective Knowledge and Community Attitudes in Tuberculosis Prevention Efforts - Lina Yunita; Rasi Rahagia; Fauziah H. Tambuala; A. Suyatni Musrah; Andi Asliana Sainal; Suprapto Suprapto (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Knowledge directly affects a person; attitudes arise due to the presence of knowledge from the individual. Tuberculosis is an infectious disease that causes death. Tuberculosis is transmitted through the air and is influenced by risk factors that play a role in transmission, such as people's attitudes, knowledge, and behaviour. This study aims to determine the influence of knowledge and community attitudes in preventing tuberculosis. The research design uses a descriptive survey with an observational approach. Accidental sampling method with a total of 52 respondents. Research instruments using questionnaires and observation sheets. Data analysis with multivariate linear regression test. The results of the statistical knowledge test with a p-value: of 0.811, an attitude of 0.599 and a multivariate logistic regression test showed that among the variables of understanding and attitude, the knowledge variable was more significantly related to efforts to prevent tuberculosis, as evidenced by the sig value. P value: 0.997 and Exp (B) 2.256. It can be concluded that the attitude and towards tuberculosis prevention efforts, but knowledge has partial value to Tubercollusis prevention efforts. Suggestions need to be made to educate them massively and continuously about tuberculosis, which are main causes, ways of transmission, and prevention.